FRI0535 Strong influence of vitamin d status on bone mineral density and bone turnover markers during weight restoration in patients with anorexia nervosa. (15th June 2017) - Giollo, A; Idolazzi, L; Caimmi, C; Fassio, A; Bertoldo, F; Grave, R Dalle; Calugi, S; Bazzani, PV; Viapiana, O; Rossini, M; Gatti, D
Abstract : Background: Anoressia nervosa (AN) is associated with an increased risk of low bone mineral density (BMD) and fractures as a consequence of an inadequate bone mass peak in adolescence and bone loss in young adulthood. Moreover, recently we have showed that vitamin D (25-OH-D) deficiency is widespread in untreated patients with AN, and there is a strong positive relationship between vitamin D status and BMD in AN. However, if vitamin D status could affect the efficacy of weight restoration in improving bone health in patients with AN is currently unknown. Objectives: Our aim was to investigate the potential role of vitamin D status in determining the efficacy on bone mineral density (BMD) of weight restoration in AN. Methods: Bone mineral density assessed by dual-energy x-ray absorptiometry (DXA), vitamin D, N-propeptide of type I collagen (P1NP), C-terminal telopeptide of type I collagen (CTX), intact parathyroid hormone (PTH) were evaluated before and after a 20-weeks intensive weight restoration therapy in patients with anorexia nervosa and secondary amenorrhoea for at least 6-months. The subjects were not receiving medications known to affect bone metabolism. Results: Ninety-one female patients aged 13–45 years old were evaluated, baseline weight 39.4±5.6 kg and BMI 15.1±1.6 kg/m 2 . Weight and BMI were significantly increased in all patients after treatment. The mean BMD values were significantly increased only at the spine (1.0±3.6%, p=0.009). A positive trend was demonstrated between post-treatment 25-OH-D and BMD changes at the spine (p=0.032). However, only the patients with post-treatment 25-OH-D ≥30 ng/ml showed significantly higher increases in BMD at the spine (2.5% vs 0.5% respectively for 25-OH-D ≥30 ng/ml and 25-OH-D <30 ng/ml, p<0.03; Figure 1 ). Both P1NP and PTH increased, whereas a significant decrease was found in 25-OH-D and CTX (p<0.05). Post-treatment CTX levels were inversely correlated with spine BMD. A positive relationship was found between changes in weight and P1NP (R2 =0.27). Conclusions: In anorexia nervosa, a hypovitaminosis D status counteracts the efficacy of the weight restoration treatment because of an increase in bone resorption mediated by a secondary hyperparathyroidism. Our study strongly support the use of vitamin D supplements for bone health in anorexia nervosa. Disclosure of Interest: None declared